Семантична спеціалізація концептів терміносфери новітніх технологій - Стасюк, Т. В. (Київський національний університет імені Тараса Шевченка, 2014)
Здійснено аналіз явища семантичної спеціалізації та переосмислення термінологічних концептів у структурі концептосфери; встановлено й обґрунтовано специфічні властивості терміносфери новітніх технологій.

The comprehensive analysis of the phenomenon of semantic specialization and recognition of term-concepts in the structure of concept-sphere is performed; the essential features of term-sphere of high technologies are determined. The article focuses on the phenomenon of semantic specialization and it rethinking of terminological concepts. The problem was not analyzed in the national linguistic science. The urgency of the issue becomes apparent after analyzing numerous changes, transformations, modifications in the structure of concepts / within the conceptual spheres faced by scholars examining the dynamics of their development.
Semantic specialization of concepts in the term sphere of high technologies
Keywords: семантична спеціалізація; концепт; термінологічний концепт; концептосфера; терміносфера; semantic specialization; concept; term-concept; concept-sphere; term-sphere